Integrated Management of Early Blight of Tomato Caused By Alternaria Solani (Journal of Plant Disease Sciences, 2023)
Tomato (Solanum lycopersicum L.) is a prominent Solanaceae vegetable and fruit crop. Due to the attack of numerous diseases produced by fungi, bacteria, viruses, and nematodes, tomato production in India is low when compared to other developed countries. The fungus Alternaria solani causes early blight at all phases of plant development and produces disease leaf blight, stem rot, fruit lesions and cause severe damage across the country. The use of anintegrated approachagainst A. solanii is the best method for managing this disease. The integrated disease management in pot culture demonstrated that the pots treated with Seed treatment with Trichoderma harzianum @ 10gm /kg + Propiconazole 25% EC (1.5/l of water) + Neem leaf extract @ 20% had the lowest disease incidence (11.77%). In contrast, the highest disease incidence was recorded in a pot sprayed alone with 20% Neem leaf extract at 20 ml/l of water (20.94%), followed by poultry manure @ 25 gm / pot (22.39%). The use of an integrated approach against A. solani is the best method for managing thisdisease.
Keywords: Tomato; Alternaria solani; Early blight; Management